(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
The purpose of this study was to determine the effectiveness of distribution of People’s Business Credit (KUR) at PT. Bank Rakyat Indonesia (Persero) Tbk. Tanah Lemo Unit, Bontobahari District, Kab. Bulukumba and the factors that support and inhibit the Distribution of KUR (People’s Business Credit) PT. Bank Rakyat Indonesia (Persero) Tbk. Tanah Lemo Unit, Bontobahari District, Kab. Bulukumba. The results of this study indicate that the effectiveness of KUR (People’s Business Credit) distribution at PT. Bank Rakyat Indonesia (Persero) Tbk. The Tanah Lemo Unit of Bonto Bahari Sub-District, Bulukumba Regency with an indicator of achieving goals, integration and adaptation can be concluded that it has a considerable influence on the development of the business of the community, but it cannot be separated from the supporting factors and there are still several factors that hinder the process of implementation.